2023
DOI: 10.3390/ijerph20032313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ambient Temperature, Relative Humidity, and Precipitation on Diarrhea Incidence in Surabaya

Abstract: Background: Diarrhea remains a common infectious disease caused by various risk factors in developing countries. This study investigated the incidence rate and temporal associations between diarrhea and meteorological determinants in five regions of Surabaya, Indonesia. Method: Monthly diarrhea records from local governmental health facilities in Surabaya and monthly means of weather variables, including average temperature, precipitation, and relative humidity from Meteorology, Climatology, and Geophysical Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A study by Kraay et al corroborated our findings that in general, the occurrence of diarrhoea is more frequent during seasons with higher rainfall [ 17 ]. In Surabaya, Indonesia, Wibawa et al [ 18 ] observed a diarrhoea incidence of 11.4 cases per 100,000 population, especially during the rainy season. In contrast, Mejiozem et al [ 19 ] concluded that lower rainfall levels and higher temperatures were associated with the highest prevalence of RoV-induced diarrhoea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Kraay et al corroborated our findings that in general, the occurrence of diarrhoea is more frequent during seasons with higher rainfall [ 17 ]. In Surabaya, Indonesia, Wibawa et al [ 18 ] observed a diarrhoea incidence of 11.4 cases per 100,000 population, especially during the rainy season. In contrast, Mejiozem et al [ 19 ] concluded that lower rainfall levels and higher temperatures were associated with the highest prevalence of RoV-induced diarrhoea.…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not calculate the correlation between RoV incidence and temperature due to minimal variation in average temperatures across different years, the available data indicates that a 1 °C increase in temperature corresponds to a 4–10% decrease in the incidence of RoV associated diarrheal disease in tropical regions [ 6 ]. RoV diarrhoea could potentially be heightened due to the favourable conditions for viral replication and survival that low temperatures provide [ 18 ]. On the contrary note, the same study also observed elevated temperatures in the western, southern, and eastern regions of Surabaya were associated with an increased risk of diarrhoea [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies considered the relations between meteorological variables, e.g. daily temperature, relative humidity, rainfall, and diarrhea, (either as individual variables or combined in various forms), including Tapp [28][29][30]. Tapp has also been applied for other health outcomes such as cardiovascular diseases and respiratory diseases [31][32][33].…”
Section: Apparent Temperature (Tapp)mentioning
confidence: 99%
“…Studies that examined viral diarrhea in relation to humidity showed inconsistent results. This inconsistent association may relate to viral pathogens (such as rotavirus diarrhea) that can survive under low and high humidity (Wibawa et al, 2023).…”
Section: Relative Humiditymentioning
confidence: 99%